Solid state chemistry of the spin transition polymers [Fe(Htrz)3](CIO4)2 and [Fe(NH2]trz)3](CIO4)2 - De Waal, Danita (University of Pretoria, 2013)
Dissertation (MSc (Chemistry))--University of Pretoria, 2006.